Notoginsenoside Fc Accelerates Reendothelialization following Vascular Injury in Diabetic Rats by Promoting Endothelial Cell Autophagy - Jingjing Liu; Chunyu Jiang; Xu Ma; Lishuai Feng; Jianbo Wang (Journal of Diabetes Research)
Interventional therapies, such as percutaneous transluminal angioplasty and endovascular stent implantation, are used widely for the treatment of diabetic peripheral vascular complications. Reendothelialization is an essential process in vascular injury following interventional therapy, and hyperglycemia in diabetes mellitus (DM) plays an important role in damaging endothelial layer integrity, leading to the retardance of reendothelialization and excessive neointimal formation. Notoginsenoside Fc (Fc), a novel saponin isolated from Panax notoginseng, effectively counteracts platelet aggregation. Nevertheless, the potential effects and molecular mechanisms of Fc on reendothelialization have yet to be explored. In this study, we present novel findings that show the benefit of Fc in accelerating reendothelialization and alleviating excessive neointimal formation following carotid artery injury in diabetic Sprague–Dawley rats in vivo. Simultaneously, the decreased autophagy of the injured carotid artery in diabetic rats was restored by Fc treatment. Our in vitro results also demonstrated that Fc promoted endothelial cell proliferation and migration under high-glucose treatment by increasing autophagy. In summary, this study supported the notion that Fc could accelerate reendothelialization following vascular injury in diabetic rats by promoting autophagy, suggesting that Fc may exert therapeutic benefits for early endothelial injury and restenosis following intervention in diabetes-associated vascular diseases.